Janus Cornarius éditeur et commentateur du traité de Galien Sur la composition des médicaments selon les lieux - Guardasole, Alessia (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2010)
The Saxon humanist Janus Cornarius (ca. 1500–1558) devoted himself to edit, translate, and comment the extant works of Galen of Pergamon (129–ca. 216). In this study I deal with the Latin translation and commentary of Galen’s work On the composition of drugs by site, edited by Cornarius (Basel, 1537). Namely, by investigating some passages of Galen’s treatise, my effort is to throw light on Cornarius’ working method, defining which literary and manuscript sources he used to improve and interpret thoroughly Galen’s text.